2013
DOI: 10.1007/s00572-013-0540-9
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of the westernmost distribution of the glaciations-surviving black truffle Tuber melanosporum

Abstract: The black truffle (Tuber melanosporum Vittad.) is an important natural resource due to its relevance as a delicacy in gastronomy. Different aspects of this hypogeous fungus species have been studied, including population genetics of French and Italian distribution ranges. Although those studies include some Spanish populations, this is the first time that the genetic diversity and genetic structure of the wide geographical range of the natural Spanish populations have been analysed. To achieve this goal, 23 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
2
16
0
1
Order By: Relevance
“…The absence of a recent bottleneck suggested that T. aestivum is not yet an endangered species, not even in Mediterranean regions since genetic group 3 is limited to southern populations (see above). A similar result was found for T. melanosporum in the Iberian Peninsula indicating a nonthreatened genetic conservation status (García-Cunchillos et al 2014). However, even under conservative scenarios, future climate changes are likely to cause further increases in mean temperature (about 2-4°C globally) with significant drought in some regions (Seager et al 2007) as well as increases in frequency and severity of extreme droughts, extreme heat levels and heat waves (IPCC 2013;Sterl et al 2008).…”
Section: T Aestivum Is Not An Endangered Speciessupporting
confidence: 69%
See 2 more Smart Citations
“…The absence of a recent bottleneck suggested that T. aestivum is not yet an endangered species, not even in Mediterranean regions since genetic group 3 is limited to southern populations (see above). A similar result was found for T. melanosporum in the Iberian Peninsula indicating a nonthreatened genetic conservation status (García-Cunchillos et al 2014). However, even under conservative scenarios, future climate changes are likely to cause further increases in mean temperature (about 2-4°C globally) with significant drought in some regions (Seager et al 2007) as well as increases in frequency and severity of extreme droughts, extreme heat levels and heat waves (IPCC 2013;Sterl et al 2008).…”
Section: T Aestivum Is Not An Endangered Speciessupporting
confidence: 69%
“…Among Tuber spp. these analyses have mainly been carried out in T. melanosporum, T. magnatum and T. brumale (Murat et al 2004(Murat et al , 2011(Murat et al , 2013Rubini et al 2004;Riccioni et al 2008;Merényi et al 2014;García-Cunchillos et al 2014). For example, a strong genetic structure with significant fixation indices was observed among T. melanosporum populations at a European scale (F st =0.20 and F st =0.177; Murat et al 2004;Riccioni et al 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These similar population genetic characteristics were explained by the “glaciation hypothesis.” In the hypothesis, the truffle populations in southern areas in Italy and Spanish acted as epibiotic species during glaciation and they spread northward along with their host trees as the ice receded (Bertault et al 1998). The research results of García-Cunchillos et al (2014) also supported this hypothesis. In this study, the Spanish populations of T. melanosporum were found to have higher genetic diversity than the Italian and French populations, with the species separated into two groups by the Iberian Mountain System (Table 1).…”
Section: Macrofungi That Require Animals For Dispersalsupporting
confidence: 53%
“…Understanding and conserving the natural diversity within truffle populations is important to future truffle culture. García-Cunchillos et al (2014) observe a high level of genetic diversity between two main groups separated by the Iberian mountain system when examining natural Spanish populations of T. melanosporum. They discuss the possibility that Spanish populations of T. melanosporum acted as a refuge during glaciation periods and later migrated to southwest France during post glaciation.…”
Section: Purpose and Content Of This Special Issuementioning
confidence: 88%